Choosing Sides: Unions and the Team Concept - Wells, Don (Labour / Le Travail, 1992)
The article reviews the book, "Choosing Sides: Unions and the Team Concept," by Mike Parker and Jane Slaughter.
Keywords: BOOKS -- Reviews; CHOOSING Sides: Unions & the Team Concept (Book); Labor; Management; Nonfiction; SLAUGHTER, Jane